Mompreneurship and resilience : Exploring entrepreneurship for mothers of children with additional needs - Casteleijn-Osorno, Regina; Hytti, Ulla (Sage, 2025)
By conducting a problematizing review, this study explores whether entrepreneurship could benefit mothers caring for children with additional needs (ANs). Through role conflict theory, we argue that entrepreneurship provides the time and space flexibility necessary to combine work and care roles and to experience the autonomy not available in paid employment. However, a supportive institutional framework, such as affordable child care, is needed. Based on role enrichment theory, we suggest that mothers caring for AN children possess skills, such as resilience and networking, which are beneficial to entrepreneurship. Furthermore, provided that a fair division of responsibilities exists within the household, AN children can strengthen the family unit and make it an important resource in entrepreneurship for mothers. We develop a future research agenda for mompreneurship with AN children in line with inclusive entrepreneurship.